1996
DOI: 10.1098/rspb.1996.0142
|View full text |Cite
|
Sign up to set email alerts
|

Auditory temporal coding in dyslexia

Abstract: Developmental dyslexia is generally believed to result from impaired linguistic processing rather than from deficits in low-level sensory function. Challenging this view, we studied the perception of non-verbal acoustic stimuli and low-level auditory evoked potentials in dyslexic adults. Compared with matched controls, dyslexics were selectively impaired in tasks (frequency discrimination and binaural unmasking) which rely on decoding neural discharges phase-locked to the fine structure of the stimulus. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
85
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(91 citation statements)
references
References 25 publications
(25 reference statements)
5
85
1
Order By: Relevance
“…Although many studies found poorer performance in dyslexics than in normal readers [4,7,10], others did not [11]. Two inter-study differences may underlie this variance.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Although many studies found poorer performance in dyslexics than in normal readers [4,7,10], others did not [11]. Two inter-study differences may underlie this variance.…”
Section: Introductionmentioning
confidence: 90%
“…According to this theory, dyslexics should have difficulties in auditory processing whenever stimuli appear in fast succession, but not when presentation rate is slower or stimuli are longer. There is substantial evidence for dyslexics' impaired performance with brief stimuli (see [6,9] for reviews); however deficits with longer stimuli were also reported [5][6][7]9]. For example, in frequency discrimination tasks, using a variety of procedures, significantly higher thresholds were found in disabled compared with agematched normal readers [4,5,7,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Across laboratories, research investigating basic auditory processing in individuals with specific language impairment (SLI) or dyslexia suggests that impaired perception and discrimination of auditory stimuli involving two or more rapidly presented transient elements hinders the development of normal language and reading abilities (Tallal and Piercy, 1974;Godfrey et al, 1981;Werker and Tees, 1987;Snowling et al, 1986;Stark and Heinz, 1996;McAnally and Stein, 1997). Further, several studies have suggested that efficient rapid auditory processing (RAP) ability is important for later language skill; performance on RAP tasks in infancy have been shown to relate to later language performance, both in normally developing infants and in those with a family history of language impairment (Benasich and Tallal, 2002;Molfese and Molfese, 1997;Trehub and Henderson, 1996).…”
Section: Behavioural Studiesmentioning
confidence: 99%